PKM PELATIHAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA DAN PEMASARAN ONLINE BAGI PELAKU USAHA ANGGOTA KOPERASI SIMPAN PINJAM BHUANA ARTHA MULIA - Dewi, I Gusti Ayu Ratih Permata; Yamawati, Ni Kd Sioaji; Nugraha, Putu Gede Wahyu Satya (UNHI Press, 2025)
The stagnant development of cooperatives is a concern for all parties, including the government and cooperative managers. Management serving the needs of non-members or the general public is considered less relevant to the welfare of cooperative members. This situation has led to management focusing on businesses oriented towards meeting member needs and failing to expand to meet the needs of non-members. Another problem faced by cooperatives in general is inadequate human resources, both in terms of cooperative knowledge, skills in managing cooperatives, and the ability to run a business. The Bhuana Artha Mulia Cooperative, which sells several basic necessities to its members, often faces challenges in financial management, particularly in terms of proper and systematic accounting records. Cooperatives still rely on manual recording or even lack bookkeeping altogether, making it difficult to accurately assess the business's financial condition. Activities implemented to address these issues include the establishment and design of a profit and loss bookkeeping system, the establishment and design of a cost of goods manufactured system, and the development of online promotional/marketing strategies.